Switching to Digital Television : UK Public Policy and the Market. - Starks, Michael (Intellect, 2006)
Between 2008 and 2012 the UK plans to turn off its conventional analogue terrestrial television and switch fully to digital TV. This is part of a trend across all the technologically advanced nations of the world. The city of Berlin led the way in 2003. The Netherlands became the first country to switch fully in 2006. Digital television was launched in the UK in 1998. Its growth has been dramatic and by no means smooth. The decision to switch fully is, at its heart, a political one: governments and regulators manage terrestrial spectrum and are ultimately responsible for switchover policy. Swi.